Learn Unity ML-Agents - Fundamentals of Unity Machine Learning : Incorporate New Powerful ML Algorithms Such As Deep Reinforcement Learning for Games. - Lanham, Micheal (Packt Publishing Ltd, 2018)
Unity Machine Learning Agents allows researchers and developers to create games and simulations using the Unity Editor which serve as environments where intelligent agents can be trained with machine learning methods through a simple-to-use Python API. This book takes you from the basics of Reinforcement and Q Learning to building Deep ...